Analysis The Application Of Health Information Systems To Health Insurance Payments: A Systematic Review - Hani Putri Febriyanti; Nurul Aini; Prasetio Hadi Pratama (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2023)
Medical informatics as a basic medical science that participates in formal medical decision-making processes is integrated with the formation of medical databases and administrative data with features of automating work process technology in health care institutions. This study aims to analyze and find out the analysis of the application of health information systems to health insurance payments. This research is a literature review sourced from several online sites such as Google Scholar, Pubmed, and Refseek by including keywords “Pharmaceutical Preparations”, “Support”, “National Health System”. The inclusion criterion used was the implementation of a health information system for payment of health insurance using the PRISMA plot diagram. The results of this study found that the implementation of health information systems for health insurance payments in health facilities is still not optimal. Many factors have affected the overall operation of the system, where the quality and quantity of human resources in handling health information systems is still lacking, the lack of facilitating facilities and infrastructure sometimes still causes disruptions and requires improvement